Availability and Reliability analysis of a system having main unit and its sub unit & two associate units (International Journal of Engineering and Computer Science, 2017)
Reliability is one of the most vital elements in Information industry. An understanding of failure process is central to any effort to model development and availability is closely related to reliability and can be calculated from reliability. Reliability measurements such as Transition Probability, Mean time to system failure, Availability and Busy period of repairman in repairing the failed units can be used to guide managerial and engineering decisions on various projects. This basic model represents a system having one main unit along with its sub unit and two of its associate units. Functioning of main unit is essential for the functioning of the system. Associate units depend on the main unit and sub unit. The system fails as soon as the main unit fails. There is a single repairman who is always available and repairs the failed unit. After a random period of time, the whole system goes for preventive maintenance. In this paper the failure and repair time distributions are taken to be exponential. Using Markov regenerative process, several system characteristics using chapman-kolmogorov equations are evaluated and profit analysis is done. This kind of analysis is of immense help to the owners of small scale industry.  Also the involvement of preventive maintenance in the model increases the reliability of the functioning units.